THE POWER OF LANGUAGE: HOW LANGUAGE SHAPES OUR WORLD - Yusupova Shukrona Olimjon qizi (Лучшие интеллектуальные исследования, 2024)
Language is a powerful tool that shapes the way we communicate, understand each other, and perceive the world around us. From the spoken word to written text, language plays a crucial role in our daily lives, influencing our thoughts, emotions, and interactions with others. In this article, we will explore the significance of language and how it impacts various aspects of our existence.